Raman spectroscopic signal reinforcement nanoparticle, raman spectroscopic signal reinforcement nanoparticle dispersion liquid, and raman spectroscopic signal reinforcement nanoparticle production method
Copper-substituted Prussian blue analogue nanoparticles address the low reproducibility issue in metal-based SERS by enhancing Raman scattering through charge transfer interactions, resulting in improved sensitivity and reproducibility of Raman spectroscopy.
Patent Information
- Application Number
- JP2023150442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
Metal-based surface-enhanced Raman spectroscopy (SERS) techniques suffer from low reproducibility of Raman scattered light enhancement effects.
Development of Raman spectroscopic signal-enhancing nanoparticles made of copper-substituted Prussian blue analogues with particle sizes between 10 to 100 nm, which enhance Raman scattering through charge transfer interactions and chemical enhancement effects.
The method achieves high reproducibility of Raman scattered light enhancement, significantly improving the sensitivity of Raman spectroscopy, as demonstrated by enhanced Raman scattering intensity and increased detection sensitivity compared to traditional SERS methods.
Smart Images

Figure 2025043114000001 
Figure 2025043114000002 
Figure 2025043114000003
Abstract
Description
[Technical field]
[0001] The present invention relates to Raman spectroscopic signal enhancing nanoparticles, a Raman spectroscopic signal enhancing nanoparticle dispersion, a dropping substrate for measuring Raman scattered light, and a method for producing Raman spectroscopic signal enhancing nanoparticles. [Background technology]
[0002] Raman spectroscopy is used to obtain chemical and structural information about materials and to measure a variety of physical properties, including stress, temperature, electrical properties, orientation, and crystallinity.
[0003] On the other hand, Raman spectroscopy has a problem of low sensitivity because the Raman scattering intensity is very weak, about one millionth of that of Rayleigh scattering. For this reason, surface-enhanced Raman spectroscopy (SERS) is known, which enhances the Raman scattering light and improves the sensitivity of Raman spectroscopy. For example, Patent Document 1 and Patent Document 2 below disclose SERS that enhances Raman scattering light using a metal nanostructure. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6196159 [Patent Document 2] Patent No. 6429318 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the case of SERS using metals, there was a problem in that the reproducibility of the enhancement effect of Raman scattering light was low.
[0006] An object of the present invention is to provide Raman spectroscopic signal enhancing nanoparticles, a Raman spectroscopic signal enhancing nanoparticle dispersion, and a method for producing Raman spectroscopic signal enhancing nanoparticles that have a high reproducibility of the enhancement effect of Raman scattered light. [Means for solving the problem]
[0007] In order to achieve the above object, the present invention includes the following embodiments. [1] A Raman spectroscopy signal enhancing nanoparticle comprising a copper-substituted Prussian blue analogue and having a particle size of 10 to 100 nm, the nanoparticle having a surface on which a substance to be measured by Raman spectroscopy is adsorbed, and which enhances Raman scattered light from the substance to be measured in light irradiated from a light source. [2] The Raman spectroscopic signal enhancing nanoparticle according to [1], wherein the copper-substituted Prussian blue analogue constituting the nanoparticle contains an atomic group that causes charge transfer to the substance to be measured adsorbed on the surface of the nanoparticle. [3] The Raman spectroscopic signal enhancing nanoparticle according to [2], wherein the atomic group is an atomic group containing a carbon-carbon, carbon-nitrogen, or carbon-oxygen bond. [4] A Raman spectroscopy signal enhancing nanoparticle dispersion liquid, in which the Raman spectroscopy signal enhancing nanoparticles according to any one of [1] to [3] are dispersed in a dispersion medium. [5]Ferricyanide ion ([Fe(CN)6] 3- ) in hydrochloric acid and divalent copper ions (Cu 2+ a step of heating a mixture of the copper-substituted Prussian blue analogue and a hydrochloric acid solution of copper(II) ions (copper(II) ions) at 80° C. for 24 hours to obtain a hydrochloric acid dispersion of the copper-substituted Prussian blue analogue; and a step of drying the hydrochloric acid dispersion of the copper-substituted Prussian blue analogue to obtain a powder of the copper-substituted Prussian blue analogue. Effect of the Invention
[0008] According to the present invention, it is possible to provide Raman spectroscopic signal enhancing nanoparticles, a Raman spectroscopic signal enhancing nanoparticle dispersion, and a method for producing Raman spectroscopic signal enhancing nanoparticles that have a high reproducibility of the enhancement effect of Raman scattered light. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing an example of the operation of the Raman spectroscopy signal enhancing nanoparticles according to an embodiment. [Diagram 2]FIG. 1 shows the results of EDS line analysis of a powder of a copper-substituted Prussian blue analogue as a nanoparticle for enhancing a Raman spectroscopic signal according to an embodiment. [Diagram 3] FIG. 1 is a diagram showing the measurement results of the binding energy of Raman spectroscopy signal enhancing nanoparticles according to an embodiment. [Figure 4] FIG. 1 is a diagram showing the measurement results of the enhancement of Raman scattered light of Raman spectroscopic signal enhancing nanoparticles according to an embodiment. [Diagram 5] FIG. 1 shows the results of Raman scattered light measurement at different concentrations of R6G, which is a substance to be measured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, modes for carrying out the present invention (hereinafter, referred to as embodiments) will be described with reference to the drawings.
[0011] An example of the operation of the Raman spectroscopy signal enhancing nanoparticle according to the embodiment is shown in Fig. 1. In Fig. 1, a substance (sample) 12 to be measured by Raman spectroscopy is adsorbed on the surface of a Raman spectroscopy signal enhancing nanoparticle 10. When excitation light 14 such as laser light is irradiated from a light source in this state, the Raman scattered light scattered from the substance to be measured 12 is enhanced by the Raman spectroscopy signal enhancing nanoparticle 10, and enhanced Raman scattered light (SERS scattered light) 16 is generated.
[0012] The Raman spectroscopic signal enhancing nanoparticles 10 are composed of copper-substituted Prussian blue analogues. The crystal structure of Prussian blue is Fe 3+ The ions form a face-centered cubic lattice, with Fe at the midpoints of each side of the cube. 2+ The ions are located at the Fe 3+ Ions and Fe 2+ Between the ions is CN - ions are present, and CN - Ionic nitrogen atom with Fe 3+ The carbon atom is coordinated to the ion, and the Fe 2+ The copper-substituted Prussian blue analogue is the Fe 3+ A part of the ions (iron (II) ions) is replaced by Cu2+ ions (copper(II) ions). 3+ ion (iron(II) ion) to Cu 2+ The chemical formula of the copper-substituted Prussian blue analogue is (K2Cu[Fe(CN)6]). 2+ ion) and iron ion (Fe 2+ Ion +Fe 3+ The atomic ratio of copper-substituted Prussian blue analogues to copper ions is approximately 1:1. Hereafter, copper-substituted PBAs will be referred to as Cu-PBAs, and PBAs as PBAs.
[0013] Furthermore, a particle size of 10 to 100 nm is suitable for the Raman spectroscopy signal enhancing nanoparticles 10. Raman spectroscopy signal enhancing nanoparticles 10 with such a particle size are advantageous for biological applications such as cell imaging.
[0014] The Raman spectroscopic signal enhancing nanoparticles 10 in this embodiment enhance Raman scattered light by a resonance effect (chemical enhancement) due to an electron (charge) transfer interaction between the nanoparticle surface and the analyte 12 adsorbed thereon. In this case, as described later, it is preferable that the Raman spectroscopic signal enhancing nanoparticles 10 contain an atomic group that causes charge transfer between the nanoparticle surface and the analyte 12, and the Fe in the crystal structure of Prussian blue is 3+ Some of the ions are Cu 2+ It is believed that the substitution with ions can increase the number of atomic groups that cause charge transfer between the Raman spectroscopy signal enhancing nanoparticles 10 and the target substance 12. Examples of the atomic groups that can be increased include atomic groups that contain bonds between carbon and carbon, carbon and nitrogen, and carbon and oxygen.
[0015] The method of using the Raman spectroscopy signal enhancing nanoparticles 10 in this embodiment is not particularly limited as long as the target substance 12 can be adsorbed on the surface, but it is preferable to disperse the Raman spectroscopy signal enhancing nanoparticles 10 in an appropriate dispersion medium for ease of handling, since this makes it easy to drop the nanoparticles on various substrates such as silicon substrates, glass substrates, metal substrates, etc. As the dispersion medium, water (demineralized water), an aqueous methanol solution, an aqueous ethanol solution, etc. are preferable.
[0016] For example, the Raman spectroscopic signal enhancing nanoparticles 10 are dispersed in the above-mentioned dispersion medium, and the measurement target substance 12 is mixed with the dispersion liquid, and the mixture is dropped onto a dropping substrate for Raman scattering light measurement, dried, and set in an appropriate Raman spectrometer to perform various measurements while enhancing the Raman scattering light. Examples of the dropping substrate for Raman scattering light measurement include a silicon substrate, carbon paper, a nickel plate, a copper plate, and a glass plate.
[0017] The Raman spectroscopy signal enhancing nanoparticles 10 according to the embodiment are made of ferricyanide ions ([Fe(CN)6] 3- ) in hydrochloric acid and divalent copper ions (Cu 2+ The copper-substituted Prussian blue analog can be produced by heating a mixture of the copper-substituted Prussian blue analog and a hydrochloric acid solution of copper(II) ions (copper(II) ions) at 80°C for 24 hours to obtain a hydrochloric acid dispersion of the copper-substituted Prussian blue analog, and drying the hydrochloric acid dispersion of the copper-substituted Prussian blue analog to obtain a powder of the copper-substituted Prussian blue analog (a powder in which nanoparticles of the copper-substituted Prussian blue analog are aggregated). EXAMPLES
[0018] Examples of the present invention will be described in detail below. Note that the following examples are provided to facilitate understanding of the present invention, and the present invention is not limited to these examples.
[0019] <Production of Nanoparticles for Enhancing Raman Spectroscopy Signals> 3 g of potassium ferricyanide (potassium hexacyanoferrate (III) K3[Fe(CN)6] manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 26 mL of hydrochloric acid (0.05 M diluted 1 M (mol / L) HCl aqueous solution manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to obtain ferricyanide ion ([Fe(CN)6] 3- A hydrochloric acid solution of Cu was prepared by dissolving 1.5 g of copper sulfate (II) (CuSO4, Fujifilm Wako Pure Chemical Industries, Ltd.) in 13 mL of hydrochloric acid (0.05 M). 2+ A solution of the ions in hydrochloric acid was prepared.
[0020] Next, a solution of ferricyanide ion in hydrochloric acid and Cu 2+ The mixture was heated at 80°C for 24 hours to separate the iron ions (Fe 3+ ions) are copper ions (Cu 2+ We synthesized copper-substituted Prussian blue analogues with substituted cations.
[0021] The copper-substituted Prussian blue analogue synthesized above was obtained in a dispersed state in hydrochloric acid, and the dispersion of the copper-substituted Prussian blue analogue (aqueous hydrochloric acid solution) was heated in an oven at 80°C for 24 hours to dry, obtaining a powder of the copper-substituted Prussian blue analogue (particle size 40 to 60 nm) as the Raman spectroscopic signal enhancing nanoparticles of the embodiment. The particle size of the powder of the copper-substituted Prussian blue analogue was measured by observing the powder with an electron microscope (field emission transmission electron microscope JEM-2100F manufactured by JEOL Ltd.).
[0022] <Evaluation of nanoparticles for enhancing Raman spectroscopy signals> The powder of the copper-substituted Prussian blue analogue as the Raman spectroscopic signal enhancing nanoparticles of the embodiment obtained as described above was subjected to line analysis using an energy dispersive X-ray analyzer (EDS) mounted on the electron microscope, and the elements at each position of an arbitrary line segment in the image were measured. The results of the line analysis are shown in Figure 2. As can be seen from Figure 2, the ratio of the detected amount of elements (iron, copper, nitrogen, carbon) at each position was almost constant, and it can be seen that copper (II) ions were introduced into the crystal lattice of Prussian blue without any variation.
[0023] Figures 3(a), (b), and (c) show the results of X-ray photoelectron spectroscopy (XPS) measurements of the Raman spectroscopic signal-enhancing nanoparticles. A JPS-9010MC XPS (AlKα radiation) manufactured by JEOL Ltd. was used for the measurements. The upper side of each figure shows copper-substituted Prussian blue analogues (Cu-PBAs), and the lower side shows Prussian blue analogues (PBAs).
[0024] Figure 3(a) shows the binding energy of the 2p orbital of the iron atom, which constitutes the crystal lattice of Prussian blue. 3+ ions and Fe 2+ ions were observed. Figure 3(b) shows the bond energy of the carbon 1s orbital, and in PBAs and Cu-PBAs, bonds such as OC=O, C=O, CN, and CC were confirmed as atomic groups. However, the emitted photoelectron intensity on the vertical axis of Figure 3(b) shows that the number of atomic groups having these bonds (especially C=O and CN) is increased compared to PBAs. Figure 3(c) shows the bond energy of the nitrogen 1s orbital, and in Cu-PBAs, bonds such as ON, pyridine-type nitrogen (denoted as pyridinicN), and cyanide nitrogen (denoted as cyanideN) were confirmed as atomic groups, and the number of these atomic groups is increased compared to PBAs.
[0025] The above-mentioned atomic groups observed in Cu-PBAs are likely to induce charge transfer in the substance to be measured by Raman spectroscopy adsorbed on the surface of the Raman spectroscopy signal enhancing nanoparticles, thereby improving the ability to enhance Raman scattered light through the resonance effect (chemical enhancement) caused by the charge transfer interaction between the surface of the Raman spectroscopy signal enhancing nanoparticles and the substance to be measured.
[0026] 4(a), (b), and (c) show the measurement results of the enhancement factor of Raman scattered light of the Raman spectroscopy signal enhancing nanoparticles according to the embodiment. FIG. 4(a) shows the Raman spectrum measured by placing a powder (sample) of rhodamine 6G (R6G obtained from Sigma-Aldrich Japan LLC) on a silicon substrate. FIG. 4(b) shows the Raman spectrum measured by using PBAs as the Raman spectroscopy signal enhancing nanoparticles, dispersing these in desalted water to a concentration of 2.5 mg / mL, and further dispersing R6G at a concentration of 5×10 -5 The Raman spectrum was measured as a comparative example after dropping a dispersion liquid (sample) in which the nanoparticles were dispersed to a concentration of 2.5 mg / mL in desalted water and adding R6G to a concentration of 5 × 10 -5 The Raman spectrum was measured as an example after dropping a dispersion liquid (sample) dispersed to obtain M on a silicon substrate and drying in the air. The Raman spectrum was obtained by setting each of the above samples in a Raman spectrometer (confocal Raman microscope RM2000 manufactured by Renishaw) and measuring the enhanced Raman scattered light. The measurement was performed using a 532 nm laser light (output 0.6 mW) with an integration time of 10 seconds.
[0027] The enhancement of Raman scattered light of the Raman spectroscopic signal enhancing nanoparticles was calculated using the following formula (1). Enhancement factor (EF) = (Isers / Ir6g) / Mf (1) Here, Isers uses Cu-PBAs and the Raman shift of 613 cm in the Raman spectrum of Figure 4(c) above. -1The peak intensity at the Raman shift of 613 cm in the Raman spectrum of R6G alone shown in Figure 4(a) above is Ir6g. -1 where M is the peak intensity at 100 nm and Mf is the mass fraction of R6G in the measurement solution. In the above examples and comparative examples, the R6G concentration is 5×10 -5 M and Mf is 2.4x10 -3 %.
[0028] From the above, the enhancement of Raman scattering light of the Raman spectroscopy signal enhancing nanoparticles using Cu-PBAs as an example is 10 7 On the other hand, the enhancement of Raman scattering light of the Raman spectroscopy signal enhancing nanoparticles using PBAs as a comparative example was found to be at the Raman shift of 613 cm in the Raman spectrum of Figure 4(b) instead of Figure 4(c). -1 The peak intensity at 10 6 As a result, it was found that the use of Cu-PBAs gave a ten-fold enhancement compared to PBAs.
[0029] <Measurement of Raman scattering enhancement effect> A measurement solution (aqueous solution) containing rhodamine 6G (R6G) as the substance to be measured at concentrations of 5 μM, 0.5 μM, and 5 nM, and a dispersion of copper-substituted Prussian blue analogues (Cu-PBAs) powder as the Raman spectroscopic signal enhancing nanoparticles according to the embodiment dispersed in desalted water at a concentration of 2.5 mg / mL were prepared, and the same volume of the dispersion was mixed with each solution (Cu-PBAs concentration was 1.25 mg / mL). This mixed solution was dropped onto a silicon wafer as a dropping substrate for Raman scattering light measurement, and then heated at 80°C on a heating plate to dry for 12 hours, and then set in a Raman spectrometer (Renishaw's confocal Raman microscope RM2000) to measure the enhanced Raman scattering light. The measurement was performed using a 532 nm laser light (output 0.6 mW) with an integration time of 10 seconds.
[0030] As a comparative example, the concentrations of R6G in the solution were set to 5 × 10 μM, 5 μM, and 0.5 (5 × 0.1) μM, and Prussian blue analogues (PBAs) with no copper substitution were used as Raman spectroscopic signal enhancing nanoparticles, and the enhanced Raman scattering light was measured in the same manner as described above.
[0031] Figures 5(a) and (b) show the measurement results of Raman scattered light. Figure 5(a) shows the measurement results of the Example, and Figure 5(b) shows the measurement results of the Comparative Example. In Figure 5(a), Raman scattered light could be measured up to an R6G concentration of 5 nM. On the other hand, in Figure 5(b), Raman scattered light could only be measured up to an R6G concentration of 5 µM. Therefore, in the Example (using a copper-substituted Prussian blue analogue), it was possible to increase the detection sensitivity by about 1000 times compared to the Comparative Example (using a Prussian blue analogue that is not copper-substituted). [Explanation of symbols]
[0032] 10 Raman spectroscopy signal enhancing nanoparticles, 12 analyte, 14 excitation light, 16 enhanced Raman scattering light.
Claims
1. Nanoparticles composed of a copper-substituted Prussian blue analogue and having a particle size of 10-100 nm, A Raman spectroscopy signal enhancing nanoparticle that enhances Raman scattered light from the substance to be measured by Raman spectroscopy when the substance is adsorbed on the surface of the nanoparticle and that is irradiated from a light source.
2. The Raman spectroscopic signal enhancing nanoparticle of claim 1 , wherein the copper-substituted Prussian blue analogue constituting the nanoparticle contains an atomic group that induces charge transfer to a substance to be measured adsorbed on the surface of the nanoparticle.
3. The Raman spectroscopy signal enhancing nanoparticle of claim 2 , wherein the atomic groups are atomic groups containing carbon-carbon, carbon-nitrogen and carbon-oxygen bonds.
4. A Raman spectroscopy signal enhancing nanoparticle dispersion liquid, comprising the Raman spectroscopy signal enhancing nanoparticles according to any one of claims 1 to 3 dispersed in a dispersion medium.
5. Ferricyanide ion ([Fe(CN) 6 ] 3- ) in hydrochloric acid solution and divalent copper ions (Cu 2+ a step of heating the mixture obtained by mixing the copper-substituted Prussian blue analogue in a hydrochloric acid solution at 80° C. for 24 hours to obtain a hydrochloric acid dispersion of the copper-substituted Prussian blue analogue; drying the hydrochloric acid dispersion of the copper-substituted Prussian blue analog to obtain a powder of the copper-substituted Prussian blue analog; 23. A method for producing a Raman spectroscopy signal enhancing nanoparticle, comprising:
Citation Information
Patent Citations
Fuel-feed controller for internal-combustion engine
JP1986096159A
Production of crude essence of plant
JP1989029318A